(untitled) (Indian Journal of Public Health Research & Development, 2020)
Health or oral health is right of every individual. Oral Health is basically a complete state of health which is free of all discomforts. A state where eating, smiling and speaking is not hampered by any kind of discomfort or disability. Rural oral health care faces challenges both ways for dentists as well as for people residing in the particular vicinity. These challenges can be listed as follows: dentist: population Ratio, literacy rate, accessibility, availability, affordability, socio – economic status, malpractice. There are few common barriers that a dentist faces while thinking of serving at a rural area. They can be summarized as safety, basic amenities, monetary constraints, lack of professional skills, distance and a compromised lifestyle. Government and various Dental Associations are making repeated efforts to overcome these challenges and pitfalls to uplift the rural oral health care.